How specific business angel makes his investment decision. An Italian case study - Iacoviello, Giuseppina (Piccola Impresa / Small Business, 2015)
The main purpose of this article is to improve understanding of the decision-making process of Business Angels, regarding in particular the criteria used in the first stage of choice of the investment. Empirical results indicate that Business Angels play a key role in facilitating the development of a business because of the financial resources they can bring and the human capital that can effectively support the entrepreneur’s choices. This article is based on an in-depth case study of an experienced Business Angel operating in Italy. Future research will continue to examine the factors characterizing the business angel’s investments. Moreover, using larger samples it will be possible to test the results of this exploratory study.